2019
DOI: 10.1002/phar.2227
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Once/Day Dolutegravir Plus Boosted Darunavir as a Switch Strategy in Heavily Treated Patients with Human Immunodeficiency Virus

Abstract: STUDY OBJECTIVE Dual therapy with once/day dolutegravir (DTG) plus boosted darunavir (DRV/b) may be a suitable and effective strategy with a high genetic barrier to resistance in patients infected with human immunodeficiency virus (HIV). Our aim was to evaluate the effectiveness of DTG plus DRV/b (DTG+DRV/b) as a switch strategy in HIV-infected patients, irrespective of their history of virologic failure (VF). DESIGN Multicenter retrospective cohort study. SETTING Human immunodeficiency outpatient treatment cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
(34 reference statements)
2
14
0
Order By: Relevance
“…Interestingly, 9/15 patients received DRV in combination with DTG; five on DRV/r plus DTG and four on DRV/c plus DTG, all nine patients were suppressed at week 48. Previous data have demonstrated good efficacy and safety of DTG plus boosted-DRV dual therapy among highly treatment-experienced patients with ARV resistance 13,14 and have found that switching from DRV/r to DRV/c results in significantly increased DTG trough concentrations. 20 This effect is presumed to be due to decreases in DTG concentrations mediated by ritonavir's induction of DTG metabolism via glucuronidation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, 9/15 patients received DRV in combination with DTG; five on DRV/r plus DTG and four on DRV/c plus DTG, all nine patients were suppressed at week 48. Previous data have demonstrated good efficacy and safety of DTG plus boosted-DRV dual therapy among highly treatment-experienced patients with ARV resistance 13,14 and have found that switching from DRV/r to DRV/c results in significantly increased DTG trough concentrations. 20 This effect is presumed to be due to decreases in DTG concentrations mediated by ritonavir's induction of DTG metabolism via glucuronidation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Real-world data from small cohorts of highly treatment-experienced patients switched to once-daily regimens of boosted DRV in combination with dolutegravir (DTG) demonstrated virologic suppression in 98-100% of patients through a median follow-up period of 12-25 months. 13,14 A minority of patients in these studies had DRV RAMs (n ¼ 12) but still achieved virologic efficacy with this treatment strategy. 13,14 One case report describes successful use of once-daily high-dose DRV and DTG in a patient with multi-drug resistant (MDR) HIV harboring three DRV RAMs to achieve virologic suppression through 18 months; however, TDM was used to guide and select a higher than standard once-daily DRV boosted with ritonavir (DRV/r) dosage (1200/100 mg) in this case.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Results from relevant studies are similar to our findings concluding that DTGþDRV/c is highly effective and well tolerated. [3][4][5][6][7] Although these studies are few, having small study populations and short follow-up, this dual therapy regimen seems very promising in HIV resistance. It has the advantage of a high genetic barrier, it is NRTI-sparing and has oncedaily administration.…”
mentioning
confidence: 99%
“…DTG+DRV/c is attractive as a salvage regimen for this population due to the absence of reverse transcriptase analogues, high genetic barrier and simplicity. 2,3…”
mentioning
confidence: 99%